Phonological Contrasts in Bahasa Indonesia and Singkil Language: Variability and Identity among Singkils - Suhery, Dedy; Kurniasy, Dessy; Idami, Zahratul; Shafridawati; Rangkuti, Rahmadsyah (LingPoet: Journal of Linguistics and Literary Research, 2025)
This paper examines the phonological differences between Bahasa Indonesia and Singkil language in linguistic variation and identity among Singkils. Language variation includes one of human language attributes which demonstrated by differences in terms of pronunciation and structure. The objectives of this research are to find out phonological similarities between Bahasa Indonesia and Singkil language, to figure out the differences in the phonological systems of both languages, and to elaborate the attitudes of Singkils students toward their language and Bahasa Indonesia. This research was conducted on the third class of SDN 1 students speaking Singkil in KutaBahari district. Ten students engaged in reading an Indonesian passage. The evidence gathered via observation, analyses of secondary data, structured interviews, and questionnaires show that the sound ᵐb, ᵐp, ⁿc, ⁿd, ⁿg, and ⁿj are not dialects at all. All speakers of Singkil pronounce words containing these sounds with the same pronunciation. It is only possible because of the influence of the language outside (other than the language of Singkil). In this case, some students pronounce [ᵐb] became[b], [ᵐp] into [p], and this is only a very small speaker of Singkil. From this condition, we can conclude that language shift occurs in bilinguals. Bilingualism began when the people move into contact with other people and languages, and also from the other needs. It can be seen from The change [ᶬp] to [p],[ⁿb] to [b],[ⁿɟ] to [ɟ] is one of the language shifts. In the end, the identity of Singkil speakers display in their language attitude towards their language based on 12 questions is mostly positive. The average value obtained was 2, 7. Meanwhile, the result indicates that the attitude of the respondents towards Indonesia is equal whether positive or negative. Keyword:PhonologicalContrasts, Bilingualism,Identity